72 SEASONAL VARIATION IN HYPERPARATHYROIDISM IN OLDER IRISH ADULTS. (25th October 2022) - Fitzpatrick, D; Laird, E; Hoey, L; Hughes, C; McNulty, H; Ward, M; Strain, JJ; Tracey, F; Molloy, A; Cunningham, C; McCarroll, K
Abstract: Background: Vitamin D deficiency is common in Ireland, varies by season and can result in secondary hyperparathyroidism. High Parathyroid Hormone (PTH) levels due to low vitamin D status are associated with increased bone turnover and lower bone mineral density, especially at cortical sites such as the hip. Given the variation in vitamin D status by time of year, our study aimed to examine for seasonal differences in hyperparthyroidism in older adults. Methods: Study participants were from a large cross-sectional study of older Irish adults recruited from hospital outpatient services and GP practices. Exclusion criteria were: eGFR< 30ml/min and elevated serum calcium (>2.5 mmol/l) in order to avoid primary hyperparathyroidism or elevated serum PTH due to advanced renal impairment. Hyperparathyroidism was defined as a PTH level > 65 ng/ml. The relationship between hyperparathyroidism and season was examined in regression models adjusting for potential factors affecting PTH. Results: There were 4324 participants, mean age 73.8 +/- 7.9 years, 65.4% were female. Hyperparathyroidism was more prevalent in Spring versus Autumn (17.4 vs 11.4 %, P = 0.0002). The increased prevalence remained after adjusting for age, gender, body mass index, timed up and go, dairy intake, eGFR, and smoking (OR 1.6, 1.2- 2.0, P=0.0003). This also corresponded to the seasonal variation in vitamin D status with deficiency (25(OH)D < 30 nmol/l) highest in Spring (23.3%) and lowest in Autumn (16.8%). Conclusion: We found that hyperparathyroidism fluctuates with season in an inverse relationship with vitamin D. Overall, high PTH levels were 60% more likely in Spring versus Autumn. This emphasises the importance of maintaining adequate vitamin D status all year round. While we adjusted for dairy intake, we did not have accurate measures of total dietary calcium intake which could also vary seasonally and be a contributory factor.